Faktor yang Mempengaruhi Hambatan Prestasi Belajar Mahasiswa BK yang Kuliah Sambil Bekerja ( Studi Kasus Terhadap Mahasiswa X ) - Ade Putra; Wira Solina; Jarudin Jarudin (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2021)
This research is motivated by students who study while working yet cannot divide their time between study and work, the objectives of this research are: 1) internal factors that affect the barriers to learning achievement of BK students who study while working, 2) external factors that affect the barriers to achievement of BK students studying while working. The type of research is descriptive qualitative case study analysis, the key informant is a student with the initials Z, additional informants consist of friends, lecturers, academic assistant lecturers and classmates, the instruments used are interview techniques, data analysis techniques used are data reduction and presentation. data. The results of the study reveal that: 1) the internal factors that affect the achievement of studying while working in college are physiological conditions in general which affect the decline in health and intelligence as seen from the decline in thinking and low motivation. 2) external factors that affect college learning achievement while working are environmental factors that come from family, friends and lecturers who are equally supportive and appreciative. It is recommended to the leadership of the Guidance and Counseling Study Program as well as related parties to be able to overcome the obstacles encountered so that student learning achievement even while working can be improved and motivation to learn back to get good results.